Analisis Tindak Tutur Dalam Film Tanah Air Beta Karya Ari Sihasale - Windy Wonmaly; Desi Susana Arwam; Tirsa Lingchin; Vicky Lendehiang; Allin Leunufna (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This study aims to determine the forms of locutionary, illocutionary, and perlocutionary speech acts contained in a film entitled "Tanah Air Beta Karya Ari Sihasale". The type of research used is descriptive qualitative. The data in this study are film speech acts while the data source is the film “Tanah Air Beta by Ari Sihasale. Data collection techniques are observing techniques and note taking techniques. The results of this study indicate that there are 3 types of speech acts, namely: namely: locutionary, illocutionary, and perlocutionary speech acts. In the film Tanah Air Beta Karya Ari Sihasale, there are 30 forms of illocutionary speech acts which are divided into 14 assertive speech acts, 13 directive speech acts, 2 expressive speech acts, 1 commissive speech act, and 3 commissive speech acts. verbal perlocutionary speech acts, 3 nonverbal perlocutionary speech acts, and 2 nonverbal perlocutionary speech acts.